NEUROGENETIC ASPECTS OF PERINATAL HYPOXIC-ISCHEMIC AFFECTIONS OF THE CENTRAL NERVOUS SYSTEM - George A. Karkashadze; Kirill V. Savostianov; Svetlana G. Makarova; Leyla S. Namazova-Baranova; Olga I. Maslova; Galina V. Yatsyk (Вопросы современной педиатрии, 2016)
Neurogenetics is a thriving young science greatly contributing to the generally accepted concept of the brain development in health and disease. Thereby; scientists are not only able to highlight new key points in traditional ideas about the origin of diseases; but also to completely rethink their view on the problem of pathology development. In particular; new data on neurogenetics of perinatal affections of the central nervous system (CNS) has appeared. Genetic factors in varying degrees affect perinatal hypoxic-ischemic CNS affections. Prematurity determination stays the most studied among them. Nevertheless; there is increasing evidence of significant epigenetic regulations of neuro-expression caused by hypoxia; malnutrition of a pregnant woman; stress; smoking; alcohol; drugs that either directly pathologically affect the developing brain; or form a brain phenotype sensitive to a perinatal CNS affection. New data obliges to change the approaches to prevention of perinatal CNS affections.